Bank monitoring incentives and optimal ABS - Pagès, Henri (Journal of Financial Intermediation, 2013)
The paper examines a continuous-time delegated monitoring problem between competitive investors and an impatient bank monitoring a pool of long-term loans subject to Markovian “contagion.” Moral hazard induces a foreclosure bias unless the bank is compensated with the right incentive-compatible contract. Fees are paid when the bank’s performance is on target and liquidation arises when the bank’s performance is sufficiently poor. I show that the optimal contract can be implemented with a whole loan sale involving both credit risk retention based on ABS credit default swaps and credit enhancement in the form of a reserve account. The optimal securitization bears out rulemaking recently proposed in the wake of the Dodd-Frank Act on a number of controversial provisions. I argue that further efficiency gains could be reaped by extending the role of the “premium capture” account into a liquidity buffer capturing performance-based compensation as a way of increasing skin in the game over the life of the transaction.